Validity and reliability of the Brazilian version of the Illness Perception Questionnaire-Revised for Dental - Marjorie Izabella Batista AGUIAR; Maria Beatriz Duarte GAVIÃO; Rogério Lacerda dos SANTOS; Renata Andréa Salvitti de Sá ROCHA; Taís de Souza BARBOSA (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract This study aimed to test the validity and reliability of the Brazilian version of the "Illness Perception Questionnaire-Revised for Dental" (IPQ-RD) in parents/guardians of children aged six to 14 years. The sample consisted of 63 parents/guardians of schoolchildren from the municipal school system of Teófilo Otoni, MG. Remote and virtual data collection consisted of self-completion of personal data, socioeconomic questionnaire and the Brazilian short versions of the "Parental-Caregiver Perceptions Questionnaire" (16-P-CPQ) and the "Family Impact Scale" (4-FIS). The IPQ-RD was applied by telephone interview. Almost half of the sample belonged to socioeconomic classes C1 and C2. Approximately 1/3 classified their child's oral health as "regular" or "poor", while 11.1% reported "strong" or "very strong" impact on their child's well-being. The items most frequently cited as having an impact on the four domains of the 16-P-CPQ were: "bad breath" (23.8%), "mouth breathing" (20.7%), "feeling anxious or afraid" (20.7%), and "paying attention at school" (10%). In the 4-FIS, 11.1% "had little time for themselves or the family". There were higher IPQ-RD scores in the "disease coherence" domain for women and lower values of "emotional dimensions" for parents/guardians with incomplete education. The mean IPQ-RD score was 126.4 (±15.1), and domain scores were positively correlated. The internal consistency was "almost perfect" for the IPQ-RD total score, ranging from "moderate" to "almost perfect" for the "child-control" and "child-consequences" domains. The intraclass correlation coefficient ranged from 0.04 (poor) to 0.68 (substantial). The Brazilian Portuguese version of the IPQ-RD proved to be valid and reliable for assessing the cognitive and emotional perception of parents/guardians about childhood dental caries.